Surround yourself with creative people: How employee narcissism connects to creativity - Guo, Qiuyun (Frontiers in Psychology, 2025)
Researchers have proposed that contextual factors in organizations can influence employee creativity and that this effect may vary as a function of employee personality. To extend the literature, this study proposed a theoretical model to explain the conditions under which narcissistic employees become more creative. This study theorizes that creative self-efficacy mediates the relationship between employee narcissism and creativity, and propose an important boundary condition—the presence of creative coworkers. Specifically, for narcissistic employees observing their coworkers engaging in creative behaviors increases their creative self-efficacy and subsequently increases their creativity. Our theoretical framework empirically tested through a study involving 247 full-time employees. The results indicate a positive relationship between employee narcissism and creative self-efficacy, which promotes creativity. Furthermore, the presence of creative coworkers moderates these relationships. This study clarifies inconsistent findings regarding the association between narcissism and creativity but also provide insight into the underlying mechanism based on social cognitive theory. This study offers managers insights into leveraging narcissistic employees—who are often considered more creative—by highlighting the critical role of creative coworkers. Managers should integrate narcissistic employees into innovation teams with highly creative peers to activate their creative potential through synergistic collaboration.